2023
DOI: 10.3390/ijms241713123
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction in PCOS: Insights into Reproductive Organ Pathophysiology

Kyle M. Siemers,
Abigail K. Klein,
Michelle L. Baack

Abstract: Polycystic ovary syndrome (PCOS) is a complex, but relatively common endocrine disorder associated with chronic anovulation, hyperandrogenism, and micro-polycystic ovaries. In addition to reduced fertility, people with PCOS have a higher risk of obesity, insulin resistance, and metabolic disease, all comorbidities that are associated with mitochondrial dysfunction. This review summarizes human and animal data that report mitochondrial dysfunction and metabolic dysregulation in PCOS to better understand how mit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…Oxidative stress hinders the production and release of SHBG by reducing the activity of HNF-4α, which could potentially play a significant role in the development of hyperandrogenism in PCOS [ 34 ]. Several studies highlight substantial mitochondrial dysfunction and heightened oxidative stress in PCOS, influencing both reproductive and transgenerational outcomes [ 35 ]. In the present study, we examined the expression of MnSOD, localized in mitochondria, emphasizing its direct relevance in addressing PCOS-associated mitochondrial issues.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress hinders the production and release of SHBG by reducing the activity of HNF-4α, which could potentially play a significant role in the development of hyperandrogenism in PCOS [ 34 ]. Several studies highlight substantial mitochondrial dysfunction and heightened oxidative stress in PCOS, influencing both reproductive and transgenerational outcomes [ 35 ]. In the present study, we examined the expression of MnSOD, localized in mitochondria, emphasizing its direct relevance in addressing PCOS-associated mitochondrial issues.…”
Section: Discussionmentioning
confidence: 99%
“…Although there were fewer reports on mitochondrial ultrastructure in PCOS patients, these authors demonstrated ultrastructural features of mitochondria including decreased number of mitochondria, decreased mitochondrial mass, increased mitochondrial fragmentation, and mitochondrial swelling and membrane defects. 27,[34][35][36] Therefore, the PCOS model is thought to mimic the phenotypes of the human PCOS through mitochondrial dysfunction. 19,20 The ovarian antral follicle consists of theca cells and granulosa cells.…”
Section: Altered Mitochondrial Functionmentioning
confidence: 99%
“…Recently, Siemers et al suggested that PCOS alters the quality and quantity of mitochondria via mitochondrial quality control, which are likely to contribute to reproductive dysfunction and transgenerational transmission. 27 Indeed, genetic, epigenetic, and genomic changes in molecules that control glycolysis, OXPHOS, mitochondrial biogenesis, mitochondrial fusion and fission dynamics, mitophagy, and apoptosis have been observed in PCOS patients and in animal models and their offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggested a possible relationship between mitochondrial dysfunction and PCOS [7,8]. Mitochondrial dysfunction in women with PCOS may contribute to metabolic abnormalities, such as insulin resistance and obesity [9,10]. Impaired mitochondrial function in PCOS may decrease energy production and increase oxidative stress, contributing to insulin resistance and hormonal imbalances [11].…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%